Relationship Between Dietary Knowledge, Socioeconomic Status, and Stroke Among Adults Involved in the 2015 China Health and Nutrition Survey - Xiang, Ruojun; Zhai, Xiaoya; Zhang, Qiujin; Wang, Zhihua (Frontiers in Nutrition, 2021)
Stroke is a public health threat that requires urgent attention in China. Nutrients have individual significant impacts on the prevalence of stroke. However, little research has been conducted on the impact of dietary knowledge on stroke and whether the impact is potentially heterogeneous under the effect of socioeconomic status. This study used the 2015 Chinese Health and Nutrition Survey to explore the impact of dietary knowledge and socioeconomic factors on populations suffering from stroke. Results indicated that risk of stroke decreased significantly with increasing dietary knowledge score. Additionally, the impact of dietary knowledge scores on the prevalence of stroke has obvious heterogeneity. First, dietary knowledge scores significantly influenced low-income groups and individuals with low educational levels. Second, the risk of stroke in fe-males is more affected by dietary knowledge. Third, for people living in different areas, dietary knowledge determines whether rural populations suffer from stroke.